Usability of Bank Capital Buffers : The Role of Market Expectations - Abad, Jose.; Garcia Pascual, Antonio (Washington, D.C. : International Monetary Fund, 2022)
Following the COVID shock, supervisors encouraged banks to use capital buffers to support the recovery. However, banks have been reluctant to do so. Provided the market expects a bank to rebuild its buffers, any draw-down will open up a capital shortfall that will weigh on its share price. Therefore, a bank will only decide to use its buffers if the value creation from a larger loan book offsets the costs associated with a capital shortfall. Using market expectations, we calibrate a framework for assessing the usability of buffers. Our results suggest that the cases in which the use of buffers make economic sense are rare in practice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Financial Institutions and Services; Micro Finance Institutions; Mortgages